Nanoformulations with Leishmania braziliensis antigens triggered controlled parasite burden in vaccinated golden hamster (Mesocricetus auratus) against visceral Leishmaniasis - Ottino, Jennifer (2022)
Leishmaniasis is a widespread vector-borne disease in Brazil, with Leishmania (Leishmania) infantum as the primary etiological agent of visceral leishmaniasis (VL). Dogs are considered the main reservoir of this parasite, whose treatment in Brazil is restricted to the use of veterinary medicines, which do not promote a parasitological cure. Therefore, efficient vaccine development is the best approach to Canine Visceral Leishmaniasis (CVL) control. With this in mind, this study used hamsters (Mesocricetus auratus) as an experimental model in an anti-Leishmania preclinical vaccine trial to evaluate the safety, antigenicity, humoral response, and effects on tissue parasite load. Two novel formulations of nanoparticles made from poly(D, L-lactic) acid (PLA) polymer loading Leishmania braziliensis crude antigen (LB) exhibiting two different particle sizes were utilized: LBPSmG (570 nm) and LBPSmP (388 nm). The results showed that the nanoparticles were safe and harmless to hamsters and were antigenic with the induction in LBSap, LBPSmG, and LBPSmG groups of total anti-Leishmania IgG antibodies 30 days after challenge, which persists 200 days in LBSap and LBPSmP. At the same time, a less pronounced hepatosplenomegaly in LBSap, LBPSmG, and LBPSmP was found when compared to control groups, as well as a less pronounced inflammatory infiltrate and granuloma formation in the spleen. Furthermore, significant reductions of 84%, 81%, and 90% were observed in spleen parasite burden accessed by qPCR in the LBSap, LBPSmG, and LBPSmP groups, respectively. In this way, LBSap, LBPSmG, and LBPSmP formulations showed better results in vaccinated and L. infantum-challenged animals in further reducing parasitic load in the spleen and attenuating lesions in liver and splenic tissues. This results in safe, harmless nanoformulation vaccines with significant immunogenic and infection control potential. In addition, animals vaccinated with LBPSmP had an overall reduction in parasite burden in the spleen, indicating that a smaller nanoparticle could be more efficient in targeting antigen-presenting cells.